2015
DOI: 10.1111/rmir.12032
|View full text |Cite
|
Sign up to set email alerts
|

Automobile Insurance Vehicle Repair Practices: Politics, Economics, and Consumer Interests

Abstract: There is a continuing debate related to insurers’ use of direct repair programs, in which they contract with particular body shops to perform insured auto repairs according to terms agreed to by the insurers and repair shop owners. A similar debate exists related to insurers specifying the use of aftermarket crash parts instead of original equipment manufacturer parts to replace damaged vehicle components, such as door panels, fenders, and hoods. This study examines these issues from a variety of perspectives … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The insurance industry is highly competitive and rivalry between organisations is fierce (Chan 2002), which leads to decreased employee wellbeing, stress and ill-health (Coetzer & Rothmann 2007). The United States and other countries have indicated that there is expected to be a shortage of skilled insurance professionals in coming years, owing to the retirement of workers, with a potential talent gap (Cole & McCullough 2012). The combined effect of demographic, social, economic and market-specific factors (Kwon 2014) contributes to retention challenges.…”
Section: The Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…The insurance industry is highly competitive and rivalry between organisations is fierce (Chan 2002), which leads to decreased employee wellbeing, stress and ill-health (Coetzer & Rothmann 2007). The United States and other countries have indicated that there is expected to be a shortage of skilled insurance professionals in coming years, owing to the retirement of workers, with a potential talent gap (Cole & McCullough 2012). The combined effect of demographic, social, economic and market-specific factors (Kwon 2014) contributes to retention challenges.…”
Section: The Contextmentioning
confidence: 99%
“…Because the insurance industry is threatened by a potential talent gap (Cole & McCullough 2012), it is crucial for international and South African insurance organisations not only to gain insight into the relationship between job satisfaction, organisational commitment and work engagement for the purpose of exploring and developing effective talent-retention strategies, but also to ensure wellbeing in general. Based on the empirical findings on job satisfaction, organisational commitment and work engagement of employees, talent-retention strategies can be formulated, not only for the insurance industry, but for organisations in general.…”
Section: The Contextmentioning
confidence: 99%
“…Internal factors consist of demand for insurance products (the size and type of demand and its variability over time), activities of insurance companies and reinsurance undertakings, regulation of the insurance market, activities of the Czech Insurance Association, mediatory activities of insurance intermediaries etc. [3,4].…”
Section: Introductionmentioning
confidence: 99%